The Future of Aid 1 : The Rise of the Undergrowth - Harford, Tim; Klien, Michael; Tilmes, Klaus (World Bank, Washington, DC, 2012)
This note considers the future of aid from the perspective of the 2005-2030 time frame. It offers a possible scenario for the future, with booming private remittances and nongovernmental aid flows put to innovative uses, eclipsing a less agile, more politically driven official aid industry. A companion note (report 32125) offers a second scenario. The notes were written in the spirit of plausible stories abougt the future to encourage thinking about possible responses.